Stabilizing agents for calibration in the determination of mercury using solid sampling electrothermal atomic absorption spectrometry - Zelinková, Hana; Červenka, Rostislav; Komárek, Josef (TheScientificWorldJournal, 2012)
Tetramethylene dithiocarbamate (TMDTC), diethyldithiocarbamate (DEDTC), and thiourea were investigated as stabilizing agents for calibration purposes in the determination of mercury using solid sampling electrothermal atomic absorption spectrometry (SS-ETAAS). These agents were used for complexation of mercury in calibration solutions and its thermal stabilization in a solid sampling platform. The calibration solutions had the form of methyl isobutyl ketone (MIBK) extracts or MIBK-methanol solutions with the TMDTC and DEDTC chelates and aqueous solutions with thiourea complexes. The best results were obtained for MIBK-methanol solutions in the presence of 2.5 g L(-1) TMDTC. The surface of graphite platforms for solid sampling was modified with palladium or rhenium by using electrodeposition from a drop of solutions. The Re modifier is preferable due to a higher lifetime of platform coating. A new SS-ETAAS procedure using the direct sampling of solid samples into a platform with an Re modified graphite surface and the calibration against MIBK-methanol solutions in the presence of TMDTC is proposed for the determination of mercury content in solid environmental samples, such as soil and plants.
Keywords: spektrofotometrie atomová; Spectrophotometry, Atomic; rtuť; Excipients; Mercury; kalibrace; Calibration; pomocné látky